2013
DOI: 10.1016/j.leukres.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden and supportive care in patients with acute leukemia

Abstract: We examined the symptoms and referral rates to specialized palliative care and psychosocial oncology services of patients with acute leukemia. The Memorial Symptom Assessment Scale (MSAS) was completed by 249 adult patients with acute leukemia. Patients reported a median of 9 physical and 2 psychological symptoms, and those with intense lack of energy, difficulty sleeping and pain were more likely to report intense worrying/sadness (P < 0.001). No patients with moderate-severe pain were referred for specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 36 publications
2
116
2
2
Order By: Relevance
“…Patients with hematologic malignancies have significant palliative care needs, including high symptom burden [15][16][17] ; however, they remain less likely than patients with solid tumors to receive specialist palliative care services and more likely to receive aggressive health care at the end of life. 18 Specifically, patients with blood cancers are less frequent users of hospice services, 19 less likely to be seen by consultative palliative care services in the hospital, 20 more likely to die in a hospital or intensive care unit, [21][22][23] and more likely to receive chemotherapy in the last few weeks of life.…”
mentioning
confidence: 99%
“…Patients with hematologic malignancies have significant palliative care needs, including high symptom burden [15][16][17] ; however, they remain less likely than patients with solid tumors to receive specialist palliative care services and more likely to receive aggressive health care at the end of life. 18 Specifically, patients with blood cancers are less frequent users of hospice services, 19 less likely to be seen by consultative palliative care services in the hospital, 20 more likely to die in a hospital or intensive care unit, [21][22][23] and more likely to receive chemotherapy in the last few weeks of life.…”
mentioning
confidence: 99%
“…Additionally, our analysis revealed that participants were affected with an overwhelming sense of loss, fear, and uncertainty in the early phase of IC [7]. Likewise, two recent cross-sectional studies on newly diagnosed AML patients receiving IC and one longitudinal study of AML patients undergoing prolonged chemotherapy documented a high prevalence of traumatic stress symptoms, intense worrying and sadness, uncertainty about durable remission, and fear of cancer recurrence as serious threat to psychological well-being [4,5,8]. Correspondingly, several qualitative studies investigating patients' perspectives on the initial phase of leukemia diagnosis, IC, and bone marrow transplantation (BMT) noted a sense of shock, emotional numbness, threat, insecurity, uncertainty, and fear regarding diagnosis, invasive procedures, cancer recurrence, and transplant rejection [9][10][11][12].…”
Section: Introductionmentioning
confidence: 70%
“…Receiving a diagnosis of AML and undergoing chemotherapy are traumatic experiences burdened with enormous physical and psychological distress [4,5,7]. Effective coping strategies are required to adjust to life with AML [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in a previous study, a high frequency of anxiety and depression was detected by the Hospital Anxiety and Depression Scale in about one-third of acute myeloid leukemia patients at diagnosis. 4 The rapid onset and fluctuating course of hematological malignancies, with frequent life-threatening complications, suggest that anxiety symptoms including posttraumatic stress disorder may be a common accompaniment. 5 Furthermore, terminal hematological cancer patients may suffer from other problems identical to those of the general cancer population, including loss of autonomy and disability.…”
Section: Optimizing End-of-life Care For Patients With Hematological mentioning
confidence: 99%